Let and be positive integers. If and are the smallest positive integers that can be written in the form of the first and the second expressions above respectively, find .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
A , B are 1 9 , 1 5 respectively(taken when m = 1 , n = 2 ), giving the answer 1 9 ⋅ 1 5 = 2 8 5 . To see why, we prove a more general result: Given positive integer p , the smallest positive integer that can be expressed as ( 2 p ) 2 m − ( 2 p − 1 ) n is 4 p − 1 , where m , n are still positive integers.
Note that p = 5 , 4 respectively for our original problem.
We consider two cases for n :
If n is even, then ( 2 p ) 2 m − ( 2 p − 1 ) n = ( 2 p ) 2 m − ( 2 p − 1 ) 2 ( 2 n ) ) = ( ( 2 p ) m − ( 2 p − 1 ) 2 n ) ( ( 2 p ) m + ( 2 p − 1 ) 2 n ) ≥ 2 p + 2 p − 1 = 4 p − 1 The inequality is valid since ( 2 p ) m − ( 2 p − 1 ) 2 n > 0 because we want a positive number and m , 2 n are positive integers. Thus, equality holds when m = 1 , n = 2 .
If n is odd, then consider the modulo 4 p of ( 2 p ) 2 m − ( 2 p − 1 ) n . Clearly ( 2 p ) 2 m ≡ 0 ( m o d 4 p ) , while ( 2 p − 1 ) n = ( 2 p ) n − n ( 2 p ) n − 1 + . . . + n ( 2 p ) − 1 ≡ n ( 2 p ) − 1 ≡ 2 p − 1 ( m o d 4 p ) by binomial expansion and ( 2 p ) k ≡ 0 ( m o d 4 p ) for k > 1 .
This means that ( 2 p ) 2 m − ( 2 p − 1 ) n ≥ 2 p − 1 . However, the equality clearly cannot hold since 2 p − 1 ∣ ( 2 p ) 2 m but ( 2 p − 1 , 2 p ) = 1 . Hence ( 2 p ) 2 m − ( 2 p − 1 ) n ≥ 4 p + 2 p − 1 = 6 p − 1 , which is greater than the lower bound we found for n is even. Thus we have proven our proposition.